Ex-Terrorist Motivation in Reeducation Program: Case Study of Terrorism Convicts in Indonesia - Nisa, Pia Khoirotun; Mustofa, Tutur Ahsanil; Albantani, Azkia Muharom; Syafri, Mohamad (TARBIYA: Journal of Education in Muslim Society, 2023)
AbstractTerrorism is one of the extraordinary crimes, creating terror based on ideological differences and misinterpreting religious teaching. This research focuses on how the re-education program for terrorist convicts is carried out and what are the factors that influence a person to be involved in criminal acts of terrorism. The research uses qualitative methods within the exploratory, investigative approach. The participants of the research are 36 terrorism convicts who are still serving their sentences. The research found that the re-education program given to terrorism convicts centered on strengthening ideology related to strong religious values and nationalism spirit. The ideological aspect is the main point in the re-education program, this is because the ideological aspect is more permanent and effective. The terrorists were still dominated by males and members of JAD (Jamaah Anshorut Daulah). The background of the individuals is also varied, ranging from uneducated to bachelor or higher, unemployed to civil servants. The convicts who join a terrorist group have different reasons. However, several reasons generally stated by convicts involved in terrorist groups are a strong belief in a particular ideology or religion, hatred of certain groups or ideologies, and the urge to make radical changes in society. In addition, convicts may also be affected by factors such as poverty, injustice, and discrimination they experienced. The research also unveils that the convicts have regret for their previous acts. Therefore, the re-education program's main role is to ensure the convicts are part of society once again.AbstrakTerorisme adalah salah satu kejahatan luar biasa yang menciptakan ketakutan berdasarkan perbedaan ideologi dan penafsiran yang salah terhadap ajaran agama. Penelitian ini berfokus pada bagaimana program reedukasi terhadap terorisme dijalankan dan faktor-faktor apa saja yang memengaruhi seseorang untuk terlibat dalam tindakan kriminal terorisme. Penelitian ini menggunakan metode kualitatif dengan pendekatan eksploratif dan investigatif. Peserta penelitian adalah 36 narapidana terorisme yang masih menjalani hukuman mereka. Penelitian menemukan bahwa program reedukasi yang diberikan kepada narapidana terorisme berpusat pada penguatan ideologi terkait nilai agama dan semangat berbangsa yang kuat. Aspek ideologis menjadi poin utama dalam program reedukasi, hal tersebut dikarenakan aspek ideologis lebih bersifat permanen dan efektif. Teroris masih didominasi oleh laki-laki dan anggota JAD (Jamaah Anshorut Daulah). Latar belakang individu-individu ini juga beragam, mulai dari yang tidak berpendidikan hingga sarjana atau lebih tinggi, dari pengangguran hingga pegawai negeri. Narapidana yang bergabung dengan kelompok teroris memiliki alasan yang berbeda. Namun, beberapa alasan yang umumnya dinyatakan oleh narapidana yang terlibat dalam kelompok teroris adalah keyakinan kuat pada ideologi atau agama tertentu, kebencian terhadap kelompok atau ideologi tertentu, dan dorongan untuk membuat perubahan radikal dalam masyarakat. Selain itu, narapidana juga dapat dipengaruhi oleh faktor-faktor seperti kemiskinan, ketidakadilan, dan diskriminasi yang mereka alami. Penelitian juga mengungkapkan bahwa para narapidana menyesal atas tindakan mereka sebelumnya. Oleh karena itu, program reedukasi menjalankan peran utamanya untuk memastikan para narapidana kembali menjadi bagian dari masyarakat.How to Cite: Nisa,P.K., Mustofa, T. A., Albantani, A.M., Syafri, M. (2023). Ex-Terrorist Motivation in Reeducation Program: Case Study of Terrorism Convicts in Indonesia. TARBIYA: Journal of Education in Muslim Society, 10(1), 69-86. doi:10.15408/tjems.v10i1.35047.